THE RELATIONSHIP BETWEEN FAMILY ROLES AND PREVENTION AND RISK OF NON-COMMUNICABLE DISEASES IN ADOLESCENTS - Sa'pang, Fransiska Anita Ekawati Rahayu; Regar, Jeanivie Chrisanta; Tandiayu, Vinsensia Reny (Jurnal Ilmiah Keperawatan, 2023)
Adolescence is a period of searching for identity and if it fails it will cause various problems such as an unhealthy lifestyle, especially during this pandemic, many teenagers are at home, physical activity is decreasing, they are at risk of experiencing non-communicable diseases (PTM) and PTM development in Indonesia continues to increase due to unhealthy lifestyles, so it takes the role of the family to be the first and main protector that is good in supporting the growth and health of adolescents. This study's objective was to determine the relationship between Family role and the prevention and risk of PTM in adolescents. This research is analytic with a cross sectional design, carried out on 19 to 23 September 2022. The population and sample are all students in first semester, a total of 90 students. The results showed that students who had a good family role, the prevention efforts of students were in the good category as many as 19 (39.6%)and students who had sufficient family roles, the risk of PTM events in adolescents was in the high risk category as many as 11 (26.2%). The results of the statistical chi-square test yielded a value of  p=0.012 it can be concluded that there is a relationship between family role and efforts to prevent non-communicable diseases and the results of the statistical chi-square test yielded a value of   p= 0.039, it can be concluded that there is a relationship between the role of the family and the risk of non-communicable diseases in adolescents in Makassar. This demonstrates that the family is crucial in efforts to prevent PTM in adolescents as soon as possible.